IL-4 receptor dependent expansion of lung CD169(+) macrophages in microfilaria-driven inflammation - Fercoq, Frédéric (PLoS Negl Trop Dis, 2019)
Lung disease is regularly reported in human filarial infections but the molecular pathogenesis of pulmonary filariasis is poorly understood. We used Litomosoides sigmodontis, a rodent filaria residing in the pleural cavity responsible for pleural inflammation, to model responses to human filarial infections and probe the mechanisms. Wild-type and Th2-deficient mice (ΔdblGata1 and Il-4receptor(r)a(-/-)/IL-5(-/-)) were infected with L. sigmodontis. Survival and growth of adult filariae and prevalence and density of microfilariae were evaluated. Cells and cytokines in the pleural cavity and bronchoalveolar space were characterized by imaging, flow cytometry and ELISA. Inflammatory pathways were evaluated by transcriptomic microarrays and lungs were isolated and analyzed for histopathological signatures. 40% of WT mice were amicrofilaremic whereas almost all mutant mice display blood microfilaremia. Microfilariae induced pleural, bronchoalveolar and lung-tissue inflammation associated with an increase in bronchoalveolar eosinophils and perivascular macrophages, production of mucus, visceral pleura alterations and fibrosis. Inflammation and pathology were decreased in Th2-deficient mice. An IL-4R-dependent increase of CD169 was observed on pleural and bronchoalveolar macrophages in microfilaremic mice. CD169(+) tissue-resident macrophages were identified in the lungs with specific localizations. Strikingly, CD169(+) macrophages increased significantly in the perivascular area in microfilaremic mice. These data describe lung inflammation and pathology in chronic filariasis and emphasize the role of Th2 responses according to the presence of microfilariae. It is also the first report implicating CD169(+) lung macrophages in response to a Nematode infection.